Pengembangan Infrastruktur Pendukung dan Pemberdayaan Sumber Daya Manusia Pengelola Desa Wisata Pucung Ngangeni - Purwanta; Arin Yusianti; Muhammad Faqih; Christy Paramitha Sabharaputri Kuncoro; Renaldi Saputra (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Pucung Village is one of the villages in Kismantoro Subdistrict, Wonogiri Regency, Central Java Province. The position of Pucung Village, which is located in the highlands and mountains, makes this area have a lot of tourism potential, such as the Watu Adeg Skyview tour. Watu Adeg Peak in Pucung Village is now a new tourist attraction in the eastern region of Wonogiri Regency that presents the beauty of the natural panorama of the border area between Central Java and East Java. From Watu Adeg Peak, visitors can see a panoramic view of Mount Lawu and the eastern region of Wonogiri. The development of tourism villages has become an important focus in efforts to advance the local tourism sector. In today's digital era, information and communication technology plays a central role in expanding the reach of promotion and enhancing interaction with local communities. This article presents a case study of the development of a tourism village website as a means to combine technology with tourism development and community empowerment efforts in Pucung Village. Through an in-depth analysis of the implementation of the village tourism website, the strategic steps in designing, developing and launching this online platform are highlighted. The results of this study illustrate the positive impacts generated and better interactions with the local community were also observed, helping in strengthening community identity and participation in the holistic development of the tourism village. In conclusion, the development of a tourism village website provides valuable insights into how the application of technology can strengthen the local tourism sector while supporting community engagement and cultural preservation.